Analysis of Seasonal Variation Characteristics of Circulation in Pearl River Estuary - HUANG Chunhua; LIU Xiaojian; GUO Huiqun; HOU Peng; CHEN Wei (Renmin Zhujiang)
Estuarine circulation controls the regional dynamic pattern,which affects the salinity,suspended sediment,and nutrient salt transport in the estuary.Based on the ocean assimilation data HYCOM,this study analyzed the seasonal variation characteristics and evolution rules of the circulation in the Pearl River Estuary and constructed the annual circulation path in the Pearl River Estuary.The results show that:①The current in the Pearl River Estuary and its adjacent waters shows obvious seasonal variation,with a change period of about one year,and as the current gets closer to the open sea,the change period is more obvious;②the open sea of the Pearl River Estuary is controlled by the circulation all the year round,which shows southwest coastal current in winter and turns to northeast upwelling current in summer due to the influence of the South China Sea warm current,of which the former accounting for about 66.5% is more than the latter accounting for about 33.5%;③the current in the Pearl River Estuary is a southwest-northeast reciprocating flow in summer and a counterclockwise circulation in winter.